Discipline Development Of Civil State Employees In Improving Community Services In Pemalang District - Hery Supriyanto (Law Development Journal, 2020)
Civil servants as servants of the state and servants of the community in carrying out their duties to provide services to the community must be equitably distributed with the ability to carry out their duties in a professional and responsible manner, by obeying their obligations and avoiding prohibitions stipulated in statutory regulations and or official regulations. Based on the above facts, it is necessary to have a scientific study in a study with the title: Fostering Discipline of Civil Servants (PNS) in Improving Community Services Based on Government Regulation Number 53 of 2010 in Pemalang Regency. The approach method used or used in this research is to use a sociological juridical approach (socio legal research). This research is a descriptive analysis research, that is, this research is a descriptive analysis research, which describes the existing situation more clearly, based on legal theory. Data analysis was carried out using qualitative analysis methods, namely an analysis carried out on the Discipline Development of Civil Servants in improving community services in Pemalang Regency.In Fostering Discipline for Civil Servants in Improving Community Service in Pemalang Regency, in general, Civil Servants as State Servants and Servants of the Community in carrying out their duties to provide services to the community must be disciplined, namely the existence of good Discipline Development for Civil Servants will create harmonious interactions, both between Civil Servants themselves and fellow bureaucratic officials as well as between employees and community members. Constraints faced Not exactly the promised time, Lack of quality of community services. in making Identity Cards (KTP) and Family Cards (KK), and for solutions to overcome Constraints / Obstacles are as follows: Implement services on time, Improve the quality of services to the community.Keywords: Civil Servant Discipline, Service to Society